2013
DOI: 10.1093/nar/gkt188
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput identification of long-range regulatory elements and their target promoters in the human genome

Abstract: Enhancer elements are essential for tissue-specific gene regulation during mammalian development. Although these regulatory elements are often distant from their target genes, they affect gene expression by recruiting transcription factors to specific promoter regions. Because of this long-range action, the annotation of enhancer element–target promoter pairs remains elusive. Here, we developed a novel analysis methodology that takes advantage of Hi-C data to comprehensively identify these interactions through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 48 publications
0
13
0
1
Order By: Relevance
“…By comparing against samples of length-matched background intervals (Methods), we found that the PIRs involved in significant interactions were enriched for overlaps with all of the active epigenomic marks in every cell line except for NHEK, where PIRs were depleted of overlaps with all annotations except H3K4me3 ( Figure 5b ). The repressive mark H3K27me3 had the smallest average enrichment (40.75%) across cell lines, suggesting that significant PIR interactions are associated with active regulatory elements (Hwang et al, 2013; Rao et al, 2014), which showed much stronger enrichments.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing against samples of length-matched background intervals (Methods), we found that the PIRs involved in significant interactions were enriched for overlaps with all of the active epigenomic marks in every cell line except for NHEK, where PIRs were depleted of overlaps with all annotations except H3K4me3 ( Figure 5b ). The repressive mark H3K27me3 had the smallest average enrichment (40.75%) across cell lines, suggesting that significant PIR interactions are associated with active regulatory elements (Hwang et al, 2013; Rao et al, 2014), which showed much stronger enrichments.…”
Section: Resultsmentioning
confidence: 99%
“…The rs71372224 SNP was however found to occur within the three overlapping binding sites for transcription factors p300 , c-Fos and c-Jun. Recent studies [30] have shown that enhancer elements have a high propensity to be bound by p300 , an enhancer-binding transcription factor. One may therefore speculate that a mutation in this putative enhancer element could influence the expression of the NF1 gene in a spatially specific manner.…”
Section: Resultsmentioning
confidence: 99%
“…One recent method used a geometric distribution- based model to form hotspots (or clusters) of adjacent Hi-C reads that represent potential sites of DNA–DNA interaction [98]. This first step was done without any consideration of read pairing that provides connection in Hi-C. Next interaction hotspots are extended by ~3 kb to account for Hi-C reads being enriched at the cut sites of the restriction enzymes used in the assay.…”
Section: Identifying the Location Of Enhancersmentioning
confidence: 99%